PENANGANAN GENANGAN SALURAN DRAINASE SEBAGAI UPAYA MENJAGA KESEHATAN MASYARAKAT PERUMAHAN YEPUPA UTAMA PERMAI DI KELURAHAN AIR DINGIN, PEKANBARU - Anas Puri; Roza Mildawati; Sri Hartati Dewi; Vella Anggreana; Harits Fajri; Indra Dipares (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activities was aimed to give preventive solution due to drainage channel inundation of As-Salaam Utama street in Yepupa Utama Permai housing area, Air Dingin Village, Bukitraya District, Pekanbaru City. Thus preventing the potential area to become a source of disease and a nest of mosquito larvae and can provide residents convenience. There were 3 points of inundation problem, namely Location 1 in the conner of As-Salaam Utama street was resolved by replacing the rectangular culvert and adjusting its elevation. Location 2 was a inundation of As-Salaam IV street was also resolved as Location 1. Location 3 was in the same condition as Loacation 2, and was handled by making a new drainage channel across the road with adjusting its elevation. The results of the activities achieved at Location 1, the inundation of water during heavy rains have been handled quite well because water can flow towards the South quite smoothly. The water flow from the North of the channel can flow smoothly to the South to the outlet after handling Location 2. Location 3 was no more puddles on the road when it rains heavely after handling. The traffic during heavy rains remains smooth and reduces the potential pavement damages.